PENGARUH PENDIDIKAN KESEHATAN DENGAN MEDIA AUDIOVISUAL TERHADAP PENGETAHUAN TENTANG FLUOR ALBUS PADA REMAJA PUTERI SMP NEGERI 9 AMBON - Sitti Suharni Hermanses; Sitti Sarifah Kotarumalos (Jurnal Kebidanan, 2022)
In Indonesia women aged 15-24 years old mostly experience vaginal discharge. There is always an increase every year up to 70% women who experienced vaginal discharge and 50% of them are adolescent. Good knowledge and care are important factors in maintaining reproductive health. Efforts to increase knowledge are carried out by providing health education. In the delivery of information there are many forms of delivery media such as audio media, print media, audio-print media, silent visual media, motion visual media, motion audiovisual media, motion visual media and audiovisual media. This research method is pre-experimental with a technique approach of One Group Pretest – Posttest Design. The population in this study were young women in grades I-II who were in SMP Negeri 9 Ambon. The sample of respondents in this study was 36 people, using a purposive sampling technique. Analysis of the data used is univariate analysis and bivariate analysis. For bivariate analysis, parametric tests were used, namely t-dependent and t-independent, which were carried out in accordance with the research objectives. The results showed that the average value of knowledge about the meaning, symptoms, causes and prevention of fluor albus increased after being given health education using audiovisual media with a p-value of 0.000 < (0.005), meaning that there was a significant effect on the mean before and after the intervention was given.